Sagot :
[tex]\large{\mathcal{SOLUTION:}}[/tex]
To find the x-intercepts , equate the function to zero and solve for the values of x
- f(x) = x(x-2)(x+5)(x+4)
- 0 = x(x-2)(x+5)(x+4)
By zero product property
- x = 0
- x-2 = 0 , x = 2
- x+5 = 0 , x = -5
- x+4 = 0 , x = -4
Therefore , the x-intercepts are 0,2,-5, and -4
[tex] \\ [/tex]
[tex]\large{\mathcal{ANSWER:}}[/tex]
- the x-intercepts are 0,2,-5, and -4
[tex] \\ [/tex]
[tex]\boxed{\begin{array}{} \blue{\text{DON'T RELY ON CHANCES,}} \\ \red{\text{ WORK FOR THE HARDEST }} \\ \end{array}}[/tex]